The development of an Integrated Marketing Dashboard in a South African business-to-business organisation - Moodley, Dhevandran (My University, 2011)
Marketing functions are under constant pressure to justify their contribution to the organisation. An inability in the past to account for their performance and contribution has resulted in marketing’s standing within the organisation being undermined. The objective of the research is to determine the key performance measures (KPMs) of a marketing function in a business-to-business (B2B) organisation that can be used to develop a marketing dashboard to improve overall marketing effectiveness. The chosen method of research for this study was a qualitative approach as the purpose of the research was to identify the metrics that were used in the integrated marketing dashboard as opposed to quantitative research that would be used for aspects such as metric calculations. The population was based on a case site which was a B2B organisation. The sample consisted of twenty respondents that were divided into ten marketers and ten non-marketers to provide feedback on key metrics that an organisation can use to develop an integrated marketing dashboard. The study found that the marketing function was not fully effective primarily due to a lack of ability to execute, poor dissemination of information on marketing initiatives and a lack of measurement systems that could measure effectiveness. It was also established that the marketing function plays a key role in other functions’ ability to achieve their objectives by providing information on product development, pricing, communication on marketing activities, development of plans, providing market intelligence, up-skilling of the sales force and channel strategies. The organisation needed to improve its feedback on marketing performance. This could be achieved through a number of avenues such as cross-functional meetings on a regular basis, monthly newsletters such as the E-Leader, periodic road-shows on new products launches and initiatives. An integrated marketing dashboard was a good way for the organisation to monitor performance of their marketing function and hold them accountable
MBA - WBS
Keywords: Marketing dashboards; Marketing